MODERN PEDAGOGICAL TECHNOLOGIES IN THE HIGHER MILITARY EDUCATION SYSTEM: EVOLUTION AND STRATEGIC PROSPECTS (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the role of modern pedagogical technologies in enhancing educational quality and shaping the professional competencies of future officer corps within higher military educational institutions (HMEIs). The intellectual and technological nature of contemporary military operations requires military pedagogy to move away from traditional approaches and transition toward the integration of innovative cyber-didactic and interactive models. The paper scientifically substantiates the military-practical significance of simulation training, artificial intelligence-based adaptive systems, and problem-based learning methodologies.
Keywords: Military pedagogy, digital learning environment, simulation technologies, VR/AR, problem-based learning, case study, case method, operational thinking, cognitive flexibility.